Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Elevated plasma phage load as a marker for intestinal permeability in leukemic patients - Xue-rui Yin; Ping Liu; Xi Xu; Ying Xia; Kai-zhao Huang; Qiong-dan Wang; Mei-mei Lai; Qi-gui Yu; Xiao-qun Zheng (Medical Microbiology and Immunology, 2020)

Reducible Fraction Dominates the Mobility of Vanadium in Soil Around an Iron Smelter - Long Zhijie; Huang Yi; Zhang Wei; Shi Zhangliang; Yu Daming; Chen Yin; Liu Chao; Wang Rui (Bulletin of Environmental Contamination and Toxicology, 2020)

Atrophy of right inferior frontal orbital gyrus and frontoparietal functional connectivity abnormality in depressed suicide attempters - Yuyin Yang; Mohammad Ridwan Chattun; Rui Yan; Ke Zhao; Yu Chen; Rongxin Zhu; Jiabo Shi; Xinyi Wang; Qing Lu; Zhijian Yao (Brain Imaging and Behavior, 2020)

Fundamental Characteristics of Tropical Rain Cell Structures as Measured by TRMM PR - Yunfei Fu; Yilun Chen; Xiangdong Zhang; Yu Wang; Rui Li; Qi Liu; Lei Zhong; Qiong Zhang; Aoqi Zhang (Journal of Meteorological Research, 2020)

Energy conservation and carbon reduction potential for solid waste in China - Minxi Wang; Zhi Li; Lu Chen; Ping Liu; Rui Zhang; Wei Liu; Yu Ma; Yajie Wang; Xin Li (Environmental Science and Pollution Research, 2020)

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Electroacupuncture improves myocardial ischemia injury via activation of adenosine receptors - Yulan Ren; Zhihan Chen; Rui Wang; Yang Yu; Dehua Li; Yonggang He (Purinergic Signalling, 2020)
Electroacupuncture (EA) can improve myocardial ischemia (MI) injury; nevertheless, the mechanism is not entirely clear. And there were disagreements about whether the effect of EA at acupoint in disease-affected meridian is better than EA at acupoint in non-affected meridian and sham acupoint. Here, we showed that the effect of EA at Neiguan (PC6) is better than EA at Hegu (LI4) and sham acupoint in affecting RPP and ECG, increasing ATP and ADO production, decreasing AMP production, and upregulating the mRNA expression levels of A1AR, A2aAR, and A2bAR; knockdown of A1AR or A2bAR reversed the effect of EA at PC6 in alleviating MI injury; knockdown of A2aAR had no influence on the cardiac protection of EA at PC6; thus, the cardioprotective effect of EA at PC6 needs A1AR and A2bAR, instead of A2aAR; considering that the cardio protection of adenosine receptor needs activation of other adenosine receptors, one of the reasons may be that after silence of A1AR or A2bAR, EA at PC6 could not impact the expression levels of the other two adenosine receptors, and after silence of A2aAR, EA at PC6 could impact the expression levels of A1AR and A2bAR. These results suggested that EA at PC6 may be a potential and effective treatment for MI by activation of A1AR and A2bAR.

Metabolomics Study of Flavonoids and Anthocyanin-Related Gene Analysis in Kiwifruit (Actinidia chinensis) and Kiwiberry (Actinidia arguta) - Min Yu; Yuping Man; Rui Lei; Xuemei Lu; Yanchang Wang (Plant Molecular Biology Reporter, 2020)
This study investigated the flavonoid compounds in Actinidia chinensis and Actinidia arguta fruits. A total of 125 flavonoids, including 9 anthocyanins, 12 catechins, 17 flavanones, 48 flavones (including 14 flavone C-glycosides), 29 flavonols, 6 isoflavones, and 4 proanthocyanidins, were identified in “Hongyang” kiwifruit (red flesh), “Jintao” kiwifruit, “Mini Amethyst” kiwiberry (purple flesh), and “Kuilv” kiwiberry. Thirty-nine metabolites showed significantly different contents between “Hongyang” and “Jintao,” and 38 of them showed higher content in “Hongyang,” whereas 39 metabolites showed significantly different contents between “Mini Amethyst” and “Kuilv,” and 31 of them showed higher content in “Mini Amethyst.” This result indicates the superior nutritional value of the pigmented kiwi cultivars in terms of flavonoids. Multivariate statistical analysis indicates that the variation in flavonoid profiles contributes to the pigmentation phenotypes of “Hongyang” and “Mini Amethyst.” Further comparative transcriptomic analysis revealed that structural genes in the anthocyanin synthesis pathway ( AcF3H , AcF3′H , AcDFR , AcUFGT ) and transcription factors ( AcMYB10 , AcbHLH5 ) may be involved in the pigmentation of the red-fleshed A. chinensis , whereas AaF3H , AaF3GT , and AaMYB110 may play important roles in the pigmentation of the purple-fleshed A. arguta . This study provides broader insight into the variation in flavonoid profiles among kiwifruit/berry, evaluates the flavonoid nutrition of the four cultivars, and provides additional evidence for the correlation between the genes and metabolites involved in flavonoid synthesis.

The abscisic acid receptor gene VvPYL4 positively regulates grapevine resistance to Plasmopara viticola - Li Liu; Chang-Yuan Liu; Hui Wang; Shu-Yi Yu; Tian-Shu Guan; Yu-Fei Huang; Rui-Chun Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Alleviation of Cd phytotoxicity and enhancement of rape seedling growth by plant growth–promoting bacterium Enterobacter sp. Zm-123 - Meng Zhang; Zonghui Jin; Xu Zhang; Guoliang Wang; Rui Li; Juanjuan Qu; Yu Jin (Environmental Science and Pollution Research, 2020)

Reconstructing the 3D digital core with a fully convolutional neural network - Qiong Li; Zheng Chen; Jian-Jun He; Si-Yu Hao; Rui Wang; Hao-Tao Yang; Hua-Jun Sun (Applied Geophysics, 2020)

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities - Tao He; Yi Liu; Rui-Feng Xiong; Xiao-Yu Li; Shou-Feng Wang; Chun-Ru Cheng (Natural Product Research, 2020)

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

Pseudomonas Saliphila sp. nov., a Bacterium Isolated from Oil-Well Production Water in Qinghai Oilfield of China - Xiao-Juan Zhang; Hong-Can Liu; Yu-Guang Zhou; Xiao-Lei Wu; Yong Nie; Qi-Rui Li; Mei-Zhu Wang; Liang Zhao; Man Cai; Ying-Qian Kang (Current Microbiology, 2020)

Spatial Variation in Thermal Stress Experienced by Barnacles on Rocky Shores: The Interplay Between Geographic Variation, Tidal Cycles and Microhabitat Temperatures - Hui-Yu Wang; Ling Ming Tsang; Fernando P. Lima; Rui Seabra; Monthon Ganmanee; Gray A. Williams; Benny K. K. Chan (Frontiers in Marine Science, 2020)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

The characteristic of the synonymous codon usage and phylogenetic analysis of hepatitis B virus - Xiaoming Qi; Chaojun Wei; Yonghong Li; Yu Wu; Hui Xu; Rui Guo; Yanjuan Jia; Zhenhao Li; Zhenhong Wei; Wanxia Wang; Jing Jia; Yuanting Li; et al. (Genes & Genomics, 2020)
Background Hepatitis B virus (HBV) infection is a crucial medical issue worldwide. The dependence of HBV replication on host cell machineries and their co-evolutionary interactions prompt the codon usage pattern of viral genes to translation selection and mutation pressure. Objective The evolutionary characteristics of HBV and the natural selection effects of the human genome on the codon usage characteristics were analyzed to provide a basis for medication development for HBV infection. Methods The codon usage pattern of sequences from different HBV genotypes of our isolates and reference HBV genome sequences downloaded from the National Center for Biotechnology Information (NCBI) database were analyzed by computing the relative synonymous codon usage (RSCU), nucleotide content, codon adaptation index (CAI) and the effective number of codons (ENC). Results The highest ENC values were observed in the C genotypes, followed by the B genotypes. The ENC values indicated a weak codon usage bias (CUB) in HBV genome. The number of codons differentially used between the three genotypes was markedly higher than that of similarly used codons. High CAI values indicated a good adaptability of HBV to its host. The ENC plot indicated the occurrence of mutational pressure in the three genotypes. The mean Ka/Ks ratios in the three genotypes were lower than 1, which indicated a negative selection pressure. The CAI and GC3% plot indicated the existence of CUB in the HBV genome. Conclusions Nucleotide composition, mutation bias, negative selection and mutational pressure are key factors influencing the CUB and phylogenetic diversity in HBV genotypes. The data provided here could be useful for developing drugs for HBV infection.

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Characterization of a Rapeseed Anthocyanin-More Mutant with Enhanced Resistance to Sclerotinia sclerotiorum - Rui Liu; Li-Na Ding; Ming Li; Wei Cao; Yu-Kang Wang; Wei-Jie Wang; Yan-Kun Yu; Zheng Wang; Ke-Ming Zhu; Xiao-Li Tan (Journal of Plant Growth Regulation, 2020)

Spent mushroom substrate combined with alkaline amendment passivates cadmium and improves soil property - Zonghui Jin; Meng Zhang; Rui Li; Xu Zhang; Guoliang Wang; Xuesheng Liu; Juanjuan Qu; Yu Jin (Environmental Science and Pollution Research, 2020)

Development of 19 novel microsatellite markers of lily-of-the-valley (Convallaria, Asparagaceae) from transcriptome sequencing - Qi-Xiang Lu; Jing Gao; Jun-Jie Wu; Xuan Zhou; Xue Wu; Meng-Di Li; Yu-Kun Wei; Rui-Hong Wang; Zhe-Chen Qi; Pan Li (Molecular Biology Reports, 2020)

Characteristics, Sources, and Risks of Polycyclic Aromatic Hydrocarbons in Topsoil and Surface Water from the Liuxi River Basin, South China - Zhenglan Xie; Lei Gao; Zuobing Liang; Jianyao Chen; Shaoheng Li; Aiping Zhu; Yu Wu; Zhigang Yang; Rui Li; Zhuowei Wang (Archives of Environmental Contamination and Toxicology, 2020)

Molecular cloning and functional characterization of the CEP RECEPTOR 1 gene MdCEPR1 of Apple (Malus × domestica) - Rui Li; Jian-Ping An; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Heritability of resistance-related gene expression traits and their correlation with body size of clam Meretrix petechialis - Fengjuan Jiang; Xin Yue; Shujing Zhang; Jiajia Yu; Rui Wang; Baozhong Liu; Hongxia Wang (Journal of Oceanology and Limnology, 2020)

Correction to: Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

Two new norneolignans from Callicarpa kwangtungensis - Hong-Yu Bi; Chun-Liang Xu; Hui-Zheng Fu; Zhi-Qiang Zhou; Rui-Jian Zhong; Mian Dai; Dong Wang (Natural Product Research, 2020)

Uptake and accumulation of pentachloronitrobenzene in pak choi and the human health risk - Ming Li; Guanghui Xu; Rui Yu; Yang Wang; Yong Yu (Environmental Geochemistry and Health, 2020)

Evaluation on activation energy of deposited clay based on thermo-gravimetric analysis (TGA) and four kinetics models - Rui-xin Yan; Jian-bing Peng; Yan-jun Shen; Yu-liang Zhang; Lin-jun Gu; Shao-kai Wang (Bulletin of Engineering Geology and the Environment, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)